Effect of Patient Transfer Training on Low Back Pain in Pre-hospital Emergency Medical Services Personnel - Kiomars Yahyaei; Khadijeh Yazdi; Shohreh Kolagari; Hosein Rahmani (Golestan University Of Medical Sciences, 2019)
Background and objectives: Pre-hospital emergency medical services (EMS) personnel are responsible for transferring patients. In case of improper patient handling, these individuals become vulnerable to various musculoskeletal problems including back pain. In this study, we aimed to evaluate the impact of an eight-hour training intervention about patient handling and transfer ergonomics on low back pain in pre-hospital EMS personnel working in the Golestan Province, Iran. Methods: This was a quasi-experimental study with a pre-test/post-test design. The study population consisted of 200 pre-hospital EMS personnel working in the Golestan Province, Iran. Overall, 40 EMS personnel were eligible to participate in the study. Data were collected using a demographic questionnaire, the Oswestry low back pain disability questionnaire and the Quebec back pain disability scale. The eight-hour training session was held by a research nurse, a physiotherapist and a physician. The subjects recompleted the Oswestry low back pain disability questionnaire and the Quebec back pain disability scale at baseline, four weeks and 12 weeks post-intervention. The collected data were analyzed using SPSS 16 and descriptive statistics. Results: The mean age, body mass index and work experience was 38.6 ± 7.6 years, 25.9 ± 3.5 kg/m2 and 8.27± 5.2 years, respectively. The mean score of functional disability reduced significantly from 35.9 ± 9 at baseline to 27.5 ± 2.5 and 19.6 ± 7 four weeks and 12 weeks after the intervention, respectively (P=0.0001). Furthermore, the mean pain score decreased from 38.7 ± 13.86 to 31.05 ± 10.75 one month post-intervention and to 22.4 ± 9.47 three months post-intervention (P=0.0001). Conclusion: Our findings suggest that training intervention on ergonomic patient transfer and patient handling can reduce the rate of lower back pain in pre-hospital EMS personnel.